Intraoral Device for Optimal Antifungal Delivery in a Rat Model - Hotta, Juliana; Cral, Wilson Gustavo; Sakima, Vinicius Tatsuyuji [UNESP]; Lara, Vanessa Soares; Urban, Vanessa Migliorini; Neppelenbroek, Karin Hermana (Bentham Science Publ Ltd, 2017)
Background: Antifungal agents incorporated into temporary denture resilient liners as drug carriers and delivery have been suggested as an alternative treatment for denture stomatitis. However, to test the in vivo biocompatibility of this protocol, standardization of an intraoral device for optimal drug delivery is required. Objective: Standardized criteria were produced to adjust an acrylic intraoral device (IOD) for rats feasible for denture stomatitis treatment by sustained drug-delivery based on minimal inhibitory drug concentrations (MICs) of antifungals for Candida albicans biofilm. Method: Adjustments methodological involved diet, impression technique, type of retention device to the palate and histopathological analysis. 115 Wistar rats were tested without IOD, with devices without relining or relined with temporary resilient material (Trusoft) modified or not by drugs at MICs (nystatin-0.032g/mL; chlorhexidine diacetate-0.064g/mL; ketoconazole-0.128g/mL). The animals were sacrificed after 7 or 14 days from the IOD installation. Results: Paste diet enabled the best animal survival conditions. The IODs that most satisfactorily remained in position were those designed only to the posterior palatal mucosa and cement-retained in molars, being all obtained from impressions highly detained and individual. In both periods, Trusoft without/with drugs showed good performance. Only histological samples from hard/soft tissues were considered appropriate for region of interest-RI determination (n=12), which corresponded to the area restricted to the first molars between the palatal neurovascular bundles. Final samples of all groups allowed a standardized descriptive histopathological analysis in both periods. Conclusion: The methodological standardization of this rat model resulted in IODs for optimal antifungal delivery for denture stomatitis treatment.
Keywords: Anti-infective agents; denture liners; drug liberation; feasibility studies; rats; stomatitis